Singlet oxygen production in Chlamydomonas reinhardtii under heat stress - Prasad, Ankush; Ferretti, Ursula; Sedlářová, Michaela; Pospíšil, Pavel (Scientific reports, 2016)
In the current study, singlet oxygen formation by lipid peroxidation induced by heat stress (40 °C) was studied in vivo in unicellular green alga Chlamydomonas reinhardtii. Primary and secondary oxidation products of lipid peroxidation, hydroperoxide and malondialdehyde, were generated under heat stress as detected using swallow-tailed perylene derivative fluorescence monitored by confocal laser scanning microscopy and high performance liquid chromatography, respectively. Lipid peroxidation was initiated by enzymatic reaction as inhibition of lipoxygenase by catechol and caffeic acid prevented hydroperoxide formation. Ultra-weak photon emission showed formation of electronically excited species such as triplet excited carbonyl, which, upon transfer of excitation energy, leads to the formation of either singlet excited chlorophyll or singlet oxygen. Alternatively, singlet oxygen is formed by direct decomposition of hydroperoxide via Russell mechanisms. Formation of singlet oxygen was evidenced by the nitroxyl radical 2,2,6,6-tetramethylpiperidine-1-oxyl detected by electron paramagnetic resonance spin-trapping spectroscopy and the imaging of green fluorescence of singlet oxygen sensor green detected by confocal laser scanning microscopy. Suppression of singlet oxygen formation by lipoxygenase inhibitors indicates that singlet oxygen may be formed via enzymatic lipid peroxidation initiated by lipoxygenase.
Keywords: Plant Proteins; Lipid Peroxidation; Heat-Shock Response; reakce na tepelný šok; peroxidace lipidů; Chlamydomonas reinhardtii; singletový kyslík; Malondialdehyde; Lipoxygenase; Singlet Oxygen; malondialdehyd; rostlinné proteiny; lipoxygenasa